Insect Management in Sugarcane - Ron H. Cherry; Thomas J. Schueneman; Gregg S. Nuessly (EDIS)
This document provides an overview of integrated pest management (IPM) strategies for sugarcane in Florida, focusing on five major insect pests: wireworms, white grubs, lesser cornstalk borers, sugarcane borers, and yellow sugarcane aphids. It details the use of resistant varieties, cultural practices, natural enemies, and insecticides to manage these pests. The document also highlights the importance of monitoring and sampling methods to determine the necessity of insecticide applications, ensuring sustainable and economically viable sugarcane production. Date first printed October 1993.